Biosurfactant evaluation heterocyclic hydrocarbon degrading marine bacteria - Lim, Kenneth Chin Chiaw (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Biosurfactants have several advantages as compared with chemically synthetic surfactants such as biodegradability, lower toxicity, environmental-friendly and have selective and specific activity under extreme temperature, pH and salinity. Eventually, biosurfactants became the 1 st choice in the food, pharmaceutical and cosmetic industrial. Apart from that, biosurfactants are also being used to enhance biodegradation activity in the polluted area. The main goal of this project is to identify strains of bacteria that are capable to degrade heterocyclic hydrocarbon while producing biosurfactant. Apart from that, the effect of additional surfactant on the biodegradation of carbazole by Thalassospira Profundimaris, strain M02 was also studied. The biodegradation rate of carbazole was measured by using spectrometer. Isolated marine bacterias and soil bacterias were cultured using heterocyclic hydrocarbon as sole carbon source. Marine bacteria which were capable to degrade heterocyclic hydrocarbon were further tested for biosurfactant production ability. In the biosurfactant evaluation, a simple and rapid, drop-collapse test was utilized. From the result, no biosurfactant was confmned from cell suspension. The addition of Tween 20 at different concentration, 0.03% and 0.06% showed enhanced biodegradation rate of carbazole by strain M02 by 140% and 233.6% respectively.